2014
DOI: 10.5935/1676-4285.20144231
|View full text |Cite
|
Sign up to set email alerts
|

Care for both mother and child immediately after childbirth: a descriptive study

Abstract: Aim:To understand the perceptions of users about the care provided to them and their newborns immediately after childbirth. Method: This is a descriptive study in which a qualitative approach was used, involving 20 postpartum women admitted to a secondary level Public Hospital of Fortaleza. Semi-structured interviews were carried out and were analyzed by means of Bardin's content analysis technique. Results: Three categories were highlighted: Care provided to newborns; care (or lack of care) provided to postpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 13 publications
(18 reference statements)
0
20
0
4
Order By: Relevance
“…This demonstrates that health education in this period focused on the child by concentrating on guidelines for breastfeeding and feeding (15) . Therefore health professionals should include in their care necessary guidance not only for the child, but also to bring together their universe of relationships, by considering the family and child as a single client.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This demonstrates that health education in this period focused on the child by concentrating on guidelines for breastfeeding and feeding (15) . Therefore health professionals should include in their care necessary guidance not only for the child, but also to bring together their universe of relationships, by considering the family and child as a single client.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that the puerperal mothers were guided by the professionals in the joint lodging and their family as to the correct handling of the breast and position of the baby during breastfeeding. These teachings contribute to the success of this practice and to the prevention of complications such as mastitis and engorgement, which may negatively affect the breastfeeding event (15) . The orientation and help provided by the puerperal woman's mother was also fundamental to successful breastfeeding, since the woman trusts the knowledge that is disseminated by her relatives and uses this to guide her caregiving.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is necessary a change in the posture of those who assist the mother and newborn, as well as a hospital organization in order to offer good structural and organizational conditions with human and material resources, in order to minimize the risk of vertical transmission. [4] In this way, the quality of care must be periodically evaluated in order to offer care able to provide the continuous reduction of the transmission of HIV from mother to newborn. With that, the assessment appears to be the best solution to get information on the functioning and effectiveness of the Health System [5].…”
Section: Introductionmentioning
confidence: 99%